P255 Diagnostic delay and economic burden in Inflammatory Bowel Disease: a single-centre experience in patients treated with biologics. (30th January 2023) - Todeschini, A; Angelini, C; Tessari, R; Ossato, A; Lunardi, G; Geccherle, A; Zuppini, T; Variola, A
Abstract: Background: Inflammatory Bowel Disease (IBD), Crohn's Disease (CD) and Ulcerative Colitis (UC), are chronic and immune-mediated diseases with a relapsing-remitting trend. The overall incidence of these diseases is increasing. However, it is estimated that more than one third of patients experienced symptoms for more than one year before diagnosis. Delay in IBD diagnosis has several clinical, therapeutic and economic implications. Early diagnosis and proper treatment are the cornerstones for improving the standard of care for these patients.This study aims to evaluate the diagnostic delay in patients with IBD and to analyze the clinical and economic burden of the delay in IBD diagnosis in patients treated with biological drugs. Methods: An observational and retrospective study was performed in IBD patients, regularly followed in our IBD Unit. Data regarding delay in IBD diagnosis were assessed through a questionnaire evaluating the disease course. Moreover, data about biologics dispensation were obtained from the medical records in the period 2014-2020. Results: 606 IBD patients were enrolled. The median delay in IBD diagnosis was 5.0 months (IQR:1.0 11.0); it was statistically lower in UC patients (4 months (IQR: 1.0 12.0)) compared to CD (6 months (IQR: 2.0 12.0)) ( p =0.041). Of these 606, 229 patients were treated with biological therapy; in this subgroup 58.9% showed a diagnostic delay. The statistical analysis showed that the diagnostic delay was statistically significant associated with biological drugs (p=0.041). Conversely, there was no association with surgical treatment. Moreover, it has appeared that the diagnostic delay is associated, with a trend of statistical significance, with need to switch or swap to other biologics (p=0.058). Regarding economic burden, patients with delayed diagnosis have significantly higher median annual cost of biological therapy than patients without diagnostic delay (€7179.26 vs € 5131.51 p= 0.009). Conclusion: The diagnostic delay in IBD represents a challenge with clinical, therapeutic and economic impact. It's crucial to cooperate with general practitioner and gastroenterologists not dedicated to IBD in order to reduce the diagnostic delay and guarantee an effective, appropriate and early treatment that will improve the patients' quality of life and meanwhile reduce the health care system costs.